2022
DOI: 10.3390/agriculture12071030
|View full text |Cite
|
Sign up to set email alerts
|

Biochar-Based Fertilizer Improved Crop Yields and N Utilization Efficiency in a Maize–Chinese Cabbage Rotation System

Abstract: Optimizing fertilization strategies is crucial for obtaining high crop yields and efficient N utilization. This study aimed to understand the potential increase in crop yield and the N utilization efficiency under biochar-based fertilizer (BF) in a maize–Chinese cabbage rotation system. Biochar-based slow-release fertilizer (BF) is an important nutrient-efficient management strategy. The yields and growth-related traits of the crops, N utilization efficiency, quality, and dynamic changes in soil inorganic N in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…In a study that used green fluorescent protein to study YL6 colonization of Chinese cabbage roots, the biomass of the colonized plants increased 400% as compared with that of noncolonized plants [31]. It was reported that N additions did not significantly improve Chinese cabbage or maize growth [32], and we found that N has no significant relationship with the Chinese cabbage growth (Figure 1a). Our findings are in accordance with those of this previous study.…”
Section: N-p-k Nutrient Management For Chinese Cabbage Growthmentioning
confidence: 61%
“…In a study that used green fluorescent protein to study YL6 colonization of Chinese cabbage roots, the biomass of the colonized plants increased 400% as compared with that of noncolonized plants [31]. It was reported that N additions did not significantly improve Chinese cabbage or maize growth [32], and we found that N has no significant relationship with the Chinese cabbage growth (Figure 1a). Our findings are in accordance with those of this previous study.…”
Section: N-p-k Nutrient Management For Chinese Cabbage Growthmentioning
confidence: 61%
“…Soil applied with 10 t ha -1 of biochar exhibited the greatest average pH compared to control soil registering lowest value (18). Incubation experiment conducted by Zhao et al (43), employing various crop straw derived biochar having varied pH from 7.69 to 10.26. The results revealed that the application of multiple biochars at 1% and 2% w/w significantly lowered the soil pH in Ultisol (pH 4.31).…”
Section: Phmentioning
confidence: 99%
“…The incorporation of biochar into soil enhances its EC. It has been demonstrated that biochars generated at higher pyrolysis temperatures, especially those derived from wood and paper waste, showcase higher EC (43). Paradoxically, this rise in alkalinity proved counterproductive, impeding the growth and development of halophytic plants.…”
Section: Electrical Conductivity (Ec)mentioning
confidence: 99%
“…crease soil fertility [4][5][6][7] as well as provide economic benefits [8,9]. Analysis of the topsoil carbon balance indicates that approximately 40% of the carbon-rich biochar appears to have been lost through mineralization, erosion, or vertical displacement [10].…”
Section: Of 16mentioning
confidence: 99%